Chitinase-3 like-protein-1, matrix metalloproteinase -9 and positive intracranial arterial remodelling - Tang, Ming; Zhou, Dongyang; He, Junhui; Bai, Hongying; Li, Qianqian; Xu, Hui (Frontiers in Aging Neuroscience, 2023)
Introduction Positive intracranial arterial remodelling is a dilated lesion of the large intracranial vessels; however, its pathogenesis is currently unknown. Some studies have identified chitinase-3 like-protein-1 (YKL-40) and matrix metalloproteinase (MMP)-9 as circulating inflammatory factors involved in positive vascular remodelling. Herein, we aimed to investigate the relationship between changes in serum YKL-40 and MMP-9 levels and positive intracranial arterial remodelling in patients with cerebral small vessel disease (CSVD). Methods A total of 110 patients with CSVD were selected. Patients with brain arterial remodelling (BAR) scores >1 times the standard deviation were defined as the positive intracranial artery remodelling group (n = 21 cases), and those with BAR scores ≤1 times the standard deviation were defined as the non-positive intracranial artery remodelling group (n = 89 cases). Serum YKL-40 and MMP-9 levels were measured using an enzyme-linked immunosorbent assay kit. Factors influencing positive intracranial artery remodelling using binary logistic regression analysis and predictive value of YKL-40 and MMP-9 for positive intracranial arterial remodelling in patients with CSVD were assessed by a subject receiver operating characteristic curve. Results Statistically significant differences in serum YKL-40 and MMP-9 levels were observed between the positive and non-positive remodelling groups (p < 0.05). The integrated indicator (OR = 9.410, 95% CI: 3.156 28.054, P<0.01) of YKL-40 and MMP-9 levels were independent risk factors for positive intracranial arterial remodelling. The integrated indicator (OR = 3.763, 95% CI: 1.884 7.517, p < 0.01) of YKL-40 and MMP-9 were independent risk factors for positive arterial remodelling in posterior circulation, but were not significantly associated with positive arterial remodelling in anterior circulation (p > 0.05). The area under the curve for YKL-40 and MMP-9 diagnostic positive remodelling was 0.778 (95% CI: 0.692–0.865, p < 0.01) and 0.736 (95% CI: 0.636–0.837, p < 0.01), respectively. Discussion Elevated serum YKL-40 and MMP-9 levels are independent risk factors for positive intracranial arterial remodelling in patients with CSVD and may predict the presence of positive intracranial arterial remodelling, providing new ideas for the mechanism of its occurrence and development and the direction of treatment.